Determinants of supplementary feeding use among commercially oriented smallholder farmers in the Eastern Cape province of South Africa - Makhura, Moraka N. (University of Pretoria, 2023)
Mini Dissertation (MSc (Agricultural Economics))--University of Pretoria, 2022.